Analisis Komparatif Mazhab al-Syafi’i dan Mazhab Maliki terhadap Praktik Qadha Puasa Oleh Ahli Waris - Riskal; Idrus, Achmad Musyahid; Syarif, Muh. Rasywan (Universitas Islam Negeri Alauddin Makassar, 2023)
This study discusses the Practice of Qadha Fasting by Heirs for the Deceased (Comparative Analysis of the Shafi'i School and the Maliki School). The main problem in this study is how the provisions for the practice of fasting qadha. How is the authority of heirs in the practice of fasting qadha according to the school of jurisprudence. What are the differences and similarities in the opinions of the jurisprudence school about the practice of fasting qadha? This type of research used is library research or literature review. This research uses qualitative research methods that are descriptive, using two data sources, namely primary data and secondary data where primary data are taken from literature such as books, journals, scientific papers such as theses, theses and so on. This study also uses a normative approach syar 'i, in analyzing content and making deductive conclusions, namely taking something that is general and drawn on a specific conception. The conclusion of the research results is that Imam Shafi'i obliges to replace fasting by paying fidyah for heirs who have passed away. Imam Malik is not obliged to fast for deceased heirs. Imam Shafi'i's istinbat method uses a method based on the Nash text of the Qur'an and Sunnah. While what is understood in establishing the law of fasting qadha for heirs who have died Imam Malik uses the qiyas method based on hadith, in a comparison of opinions, Imam Shafi'i argues that it is mandatory to replace it by paying fidyah for heirs who have passed away while Imam Malik argues that his guardian is not obliged to fast to bear all the fasts left by the mayit, except when the mayit while still alive wills to change his fast.